2017
DOI: 10.1136/emermed-2017-206727
|View full text |Cite
|
Sign up to set email alerts
|

PREDICT prioritisation study: establishing the research priorities of paediatric emergency medicine physicians in Australia and New Zealand

Abstract: This prioritisation process has established a list of research questions, which will inform multicentre PEM research in Australia and New Zealand. It has also emphasised the importance of the translation of new knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 22 publications
1
61
2
Order By: Relevance
“…When comparing our results with prior initiatives in PEM there is some alignment in research topics. For example, pain and sedation, respiratory illnesses/wheeze, patient safety/medication error, and sepsis were identified as priorities in our work and prior publications . Major/multisystem trauma were also priorities identified in our work and in the UK and Ireland and Australia and New Zealand .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…When comparing our results with prior initiatives in PEM there is some alignment in research topics. For example, pain and sedation, respiratory illnesses/wheeze, patient safety/medication error, and sepsis were identified as priorities in our work and prior publications . Major/multisystem trauma were also priorities identified in our work and in the UK and Ireland and Australia and New Zealand .…”
Section: Discussionmentioning
confidence: 73%
“…Table shows the topics and rankings from this process compared to prior research priority setting initiatives in the ED setting …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It also features prominently among the top research priorities identified by emergency physicians in the UK, Australia and New Zealand. 2,3 The amount of fluid given in sepsis has changed over the past two decades. Early goal-directed therapy (EGDT) decreased sepsis mortality in ED patients in a small, single-centre study in the USA published in 2001.…”
Section: Introductionmentioning
confidence: 99%